Hemostatic Challenges in Neonates - Davenport, Patricia; Sola-Visner, Martha (Frontiers in Pediatrics, 2021)
The neonatal hemostatic system is strikingly different from that of adults. Among other differences, neonates exhibit hyporeactive platelets and decreased levels of coagulation factors, the latter translating into prolonged clotting times (PT and PTT). Since preterm neonates have a high incidence of bleeding, particularly intraventricular hemorrhages, neonatologists frequently administer blood products (i.e. platelets and FFP) to non-bleeding neonates with low platelet counts or prolonged clotting times in an attempt to overcome these “deficiencies” and reduce bleeding risk. However, it has become increasingly clear that both the platelet hyporeactivity as well as the decreased coagulation factor levels are effectively counteracted by other factors in neonatal blood that promote hemostasis (i.e. high levels of vWF, high hematocrit and MCV, and reduced levels of natural anticoagulants), resulting in a well-balanced neonatal hemostatic system, perhaps slightly tilted toward a prothrombotic phenotype. While life-saving in the presence of active major bleeding, the administration of platelets and/or FFP to non-bleeding neonates based on laboratory tests has not only failed to decrease bleeding, but has been associated with increased neonatal morbidity and mortality in the case of platelets. In this review, we will present a clinical overview of bleeding in neonates (incidence, sites, risk factors), followed by a description of the key developmental differences between neonates and adults in primary and secondary hemostasis. Next, we will review the clinical tests available for the evaluation of bleeding neonates and their limitations in the context of the developmentally unique neonatal hemostatic system, and will discuss current and emerging approaches to more accurately predict, evaluate and treat bleeding in neonates.